Endogenous control miRNAs for normalization in plasma samples of Alzheimer's disease patients from a discovery and validation cohort. (31st December 2021) - Dakterzada, Faride; Targa, Adriano; Benitez, Ivan David; Torres, Gerard; ElKhayat, Leila Romero; Moncusi, Anna; Huerto, Raquel; Barbe, Ferran; Piñol‐Ripoll, Gerard
Abstract: Background: Several studies had explored the role of miRNAs in Alzheimer's disease (AD). The identification of endogenous controls (ECs) would contribute to the standardization of these biomarkers in AD but they have not yet been established. The objective of the study was to identify miRNAs that can be used as ECs in AD. Method: We evaluated 145 patients divided into two different cohorts. One was a discovery cohort of 19 women diagnosed with mild to moderate AD (Mini‐Mental State Examination (MMSE) score ≥ 20) and with confirmed pathologic levels of Aβ42 in CSF. The stability assessment cohort consisted of 126 individuals: 24 control subjects, 25 subjects with MCI and negative for CSF biomarkers, 22 subjects with MCI and positive for CSF biomarkers and 55 subjects with AD and positive for CSF biomarkers. In the discovery cohort, a profile of 384 miRNAs was determined in plasma by TaqMan Low Density Array. The best EC candidates were identified by mean‐centering and concordance correlation restricted normalization methods. The stability of the EC candidates was assessed using the GeNorm, BestKeeper and NormFinder algorithms. Result: Nine miRNAs (hsa‐miR‐324‐5p, hsa‐miR‐22‐5p, hsa‐miR‐103a‐2‐5p, hsa‐miR‐362‐5p, hsa‐miR‐425‐3p, hsa‐miR‐423‐5p, hsa‐let‐7i‐3p, hsa‐miR‐532‐5p, and hsa‐miR‐1301‐3p) were identified as EC candidates in the discovery cohort. The validation results indicated that hsa‐miR‐103a‐2‐5p was the best EC, followed by hsa‐miR‐22‐5p, hsa‐miR‐1301‐3p, and hsa‐miR‐425‐3p, which had similar stability values in all three algorithms. Conclusion: We identified a profile of four miRNAs as potential plasma ECs to be used for normalization of miRNA expression data in studies of subjects with cognitive impairment.